2022
DOI: 10.3171/2021.11.focus21586
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system injury–induced immune suppression

Abstract: Central nervous system trauma is a common cause of morbidity and mortality. Additionally, these injuries frequently occur in younger individuals, leading to lifetime expenses for patients and caregivers and the loss of opportunity for society. Despite this prevalence and multiple attempts to design a neuroprotectant, clinical trials for a pharmacological agent for the treatment of traumatic brain injury (TBI) or spinal cord injury (SCI) have provided disappointing results. Improvements in outcome from these di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 76 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…It may be that even mild CNS injuries can lead to both a weakened immune system, and thus susceptibility to infection, and ADRD-associated neuronal damage accumulation. 49 Further, cognition was measured at only one time point in this study, but studies that investigated HSV and CMV independently showed infected individuals had faster cognitive decline over an extended follow-up time. 18,48 We anticipate addressing this with the completion of Wave 5.5 of the ECA.…”
Section: Discussionmentioning
confidence: 94%
“…It may be that even mild CNS injuries can lead to both a weakened immune system, and thus susceptibility to infection, and ADRD-associated neuronal damage accumulation. 49 Further, cognition was measured at only one time point in this study, but studies that investigated HSV and CMV independently showed infected individuals had faster cognitive decline over an extended follow-up time. 18,48 We anticipate addressing this with the completion of Wave 5.5 of the ECA.…”
Section: Discussionmentioning
confidence: 94%
“…Pitsch et al demonstrated spontaneous recurrent seizures and persisting memory deficits, and the sclerotic hippocampus was populated with CD8 + T-cells escorted by NK-cells [ 33 ]. MDSCs can inhibit other immune cells, including T-, B-, and NK-cells, and are closely related to many nervous system diseases [ 34 , 35 ]. Taken together, differentially expressed IRGs and IRG-related DEGs were likely associated with neuroinflammation and the immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the acute phase, microglia remain phenotypically activated [ 29 ], inducing long-term inflammation that serves as a link between acute illness and chronic neurodegeneration and symptomatic cognitive impairment and dementia [ 30 ]. TBI-induced immunosuppression is not fully understood but is hypothesized to be the result of the downregulation of leukocyte activity in response to DAMP release and inflammasome activation [ 31 ].…”
Section: Pathophysiology Of Malnutrition After Acute Brain Injurymentioning
confidence: 99%